Competition and Innovation: Evidence from Financial Services - Jaap W.B. Bos; J. Kolari; R. van Lamoen (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2009)
In this paper we seek to contribute to the literature on competition and innovation by focusing on individual firms within the U.S. banking industry in the period 1984-2004. We measure innovation by estimating technology gaps and find evidence of an inverted-U relationship between competition and the technology gaps in banking. This finding is robust over several different specifications and is consistent with theoretical and empirical work by Aghion, Bloom, Blundell, Griffith, and Howitt (2005b). The optimal amount of innovation requires a slightly positive mark up. Also, we find that the U.S. banking industry as a whole has consolidated beyond this optimal innovation level and that state-level interstate banking deregulation has lowered innovation.
Keywords: 330; competition; innovation; stochastic frontier analysis; technology gap ratio; banking